ANALISIS KEUANGAN INDUSTRI KREATIF KECAMATAN ANDIR (Studi Kelurahan Kebon Jeruk) - Mohammad Benny Alexandri; Ria Arifianti; Agus Taryana (Jurnal Penelitian dan Pengabdian Kepada Masyarakat (JPPM), 2022)
The existence of the Covid-19 pandemic has disrupted various sectors of human life, including the economic sector  such as Micro, small and medium enterprises (MSMEs) are explicitly feeling the impact. Various policies issued by the government in an effort to stop the spread of the Covid-19 outbreak, require business actors to be able to adapt to the existing situation. The limitation of operating hours which leads to a decrease in income can be said to be one of the most felt impacts by business actors. This is also experienced by creative industry entrepreneurs in Kebon Jeruk Village, Andir District, Bandung City. Creative industry businesses that are driving the economy in Kebon Jeruk Village have stalled due to the Covid-19 pandemic. In response to this condition, various ways are needed to overcome it. One of them is an understanding of financial analysis.The method of community service is to use the method of preparation stages, implementation stages and follow-up stages. The preparation stage begins with discussing the division of the group and the area to be addressed, preparing the things needed to conduct interviews and asking for help from several parties to deliver to the location you want to go to. Stages of implementation After the preparation is complete, the team that has been divided then goes to the location that has been previously determined. Arriving at the creative industry shop in question, the team representative asked for permission to interview and collect some data from there. After getting permission, we then interviewed the owner or employees in the shop. Follow-up stages The follow-up of this activity is to collect interim reports, in the form of interviews and some documentation to serve as a reference for financial analysis.The results obtained are that through financial analysis activities will help business actors in assessing and knowing the financial condition of the business, business actors can find out how far their business is able to survive in the midst of the Covid-19 pandemic situation, in addition to restoring creative industry businesses in the midst of the Covid-19 pandemic situation. Creative efforts are needed through the use of technological developments in disseminating information at this time, it can be used to expand the promotion of a business product, even tourist destinations. Keberadaan pandemi Covid-19 mengganggu berbagai sektor kehidupan manusia, tak terkecuali sektor perekonomian. Usaha mikro, kecil dan menengah (UMKM) secara eksplisit merasakan dampaknya. Berbagai kebijakan yang dikeluarkan pemerintah dalam upaya memutus penyebaran wabah Covid-19, mengharuskan pelaku usaha untuk mampu beradaptasi dengan situasi yang ada. Pembatasan jam operasional yang bermuara pada menurunnya pendapatan dapat dikatakan menjadi salah satu dampak yang paling terasa oleh pelaku usaha. Hal ini turut dialami pula oleh pelaku usaha industri kreatif di Kelurahan Kebon Jeruk, Kecamatan Andir, Kota Bandung. Usaha industri kreatif yang menjadi penggerak perekonomian di Kelurahan Kebon Jeruk, tersendat akibat kondisi pandemi Covid-19. Menyikapi kondisi tersebut, dibutuhkan berbagai cara guna mengatasinya. Salah satunya ialah pemahaman akan analisis keuangan.Metode pengabdian pada masyarakat adalah menggunakan metode tahapan persiapan, tahapan pelakasanaan dan tahapan tindak lanjut. Tahapan Persiapan dimulai dengan berdiskusi mengenai pembagian kelompok serta wilayah yang akan dituju, mempersiapkan hal-hal yang diperlukan untuk melakukan wawancara dan meminta bantuan beberapa pihak untuk mengantarkan ke lokasi yang ingin dituju. Tahapan pelaksanaan Setelah persiapan sudah matang, tim yang sudah dibagi kemudian berangkat ke lokasi yang sudah ditetapkan sebelumnya. Sesampainya di toko industri kreatif yang dimaksud, perwakilan tim meminta izin untuk memawancarai dan mengabil beberapa data dari sana. Setelah mendapat izin, selanjutnya kami mewawancarai pemilik ataupun pegawai yang ada di toko tersebut. Tahapan tindak lanjut Tindak lanjut dari kegiatan ini adalah mengumpulkan laporan sementara, berupa hasil wawancara dan beberapa dokumentasi untuk dijadikan sebagai acuan analisis keuangan.Hasil yang didapat adalah melalui kegiatan analisis keuangan akan membantu pelaku usaha dalam menilai dan mengetahui kondisi keuangan usaha tersebut, pelaku usaha dapat mengetahui sejauh mana usahanya mampu bertahan di tengah situasi pandemi Covid-19, selain itu guna memulihkan usaha industri kreatif di tengah situasi pandemi Covid-19 diperlukan usaha kreatif melalui pemanfaatan perkembangan teknologi dalam menyebarkan informasi pada saat ini, dapat digunakan untuk memperluas promosi suatu produk usaha, bahkan destinasi wisata sekalipun.